A Mid-Infrared Dual-Band Filter With Ultra-High Resolving Power - Xin He; Jinliang Jie; Junbo Yang; Yunxin Han; Sen Zhang (IEEE Photonics Journal, 2020)
A mid-infrared (mid-IR) dual-band filter with ultra-high resolving power is designed and numerically investigated. It is composed of an Al2O3 layer between a gold grating and a CaF2 substrate. Each unit cell of the grating consists of two gold strips with different heights. The filter provides two high-extinction ultra-narrow stop bands. One is at a wavelength of ~3.8392 μm with a full-width at half-maximum (FWHM) of ~0.8 nm, and the other is at a wavelength of ~3.8435 μm with a FWHM of ~1.8 nm. The resolving power of the filter is >2100. The two stop bands result from the (+1) and (-1) waveguide modes, respectively. An interaction between the two resonance modes exists and affects the stop bands. We can control the interaction by adjusting the grating parameters, thus designing the FWHMs and lineshapes of the two stop bands flexibly.